Pengaruh Penggunaan Bahasa Gaul di Platform X Terhadap Gaya Komunikasi Digital Generasi Z - Arfiyanto, Yolanda Alea; Haloho, Donna Anggita Mayra; Zufar, Firyal Sabbiha (Lentera Jurnal Manajemen, 2025)
In the era of digital communication, slang has become an essential part of Generation Z’s communication style, especially on platform X. This study aims to analyze the impact of slang usage on the digital communication style of Generation Z using a Systematic Literature Review (SLR) approach. The findings show that slang is not only a communication tool but also serves as a means of self-expression, social identity, and emotional closeness among users. However, excessive use may negatively affect formal language skills. Therefore, adaptive language literacy awareness is necessary to ensure digital communication remains relevant and effective. This study concludes that slang reflects social dynamics and linguistic development in the digital age, emphasizing the need to balance language creativity and linguistic norms.